Effectiveness of Protein-enriched oral nutritional supplements on muscle function in middle-aged and elderly women: A randomized controlled trial - Minji Kang; Hyunkyung Rho; Minhui Kim; Miji Lee; Yunsook Lim; Jinmann Chon; Hyunjung Lim (The Journal of Nutrition, Health and Aging)
Objectives: This study evaluated the effects of protein-enriched oral nutritional supplementation (ONS) consumption for 12 weeks on muscle mass, muscular strength, and function in middle-aged and elderly women. Design: A single-center, double-blind, randomized controlled trial Participants: This study was conducted with 70 healthy female participants aged 50–80. Intervention and measurements: Participants were instructed to incorporate two daily packs of either the test ONS (Nucare Active, Daesang Wellife Corp., Seoul, Republic of Korea; 200 kcal/pack, 23 g carbohydrate, 6 g fat, and 15 g protein including branched chain amino acids or placebo ONS (200 kcal/pack, 33 g carbohydrate, 8 g fat, and 1 g protein) into their routine for 12 weeks while maintaining their regular lifestyle. The primary outcome was lean body mass (LBM), while secondary outcomes included muscular strength, physical performance ability, inflammatory markers, and body fat mass (FM). Results: Sixty-four participants (33 in the test group, 31 in the placebo group; mean ± SD age, [test] 63.06 ± 5.51 years, [placebo] 63.29 ± 3.28 years, p = 0.839) completed the 12-week protocol. The test group exhibited a higher percentage change in LBM than the placebo group (0.26 % [95%CI: −0.27, 0.78] vs. −0.47 % [95%CI: −0.81, −0.13]; p = 0.020). The placebo group experienced a significant increase in FM (38.15 % [95%CI: 36.62, 39.69] to 38.67 % [95%CI: 37.14, 40.21]; p < 0.01). The difference in the changes in LBM/BMI and FM/BMI between the two groups was also visually distinct. There were no significant differences between the two groups in terms of muscular strength, physical performance ability, or inflammatory markers. Conclusions: Protein-enriched ONS helped maintain LBM and prevent FM gain in middle-aged and elderly females. This suggests its potential role in preventing frailty and musculoskeletal disorders associated with female aging.